THE RELATIONSHIP OF THE CADRES WITH THE EFFORT TO INCREASE OF POSYANDU SERVICES IN KALIKEBO VILLAGE SUB – DISTRICT TRUCUK KLATEN - Siti Fatimah; Kemaludin .; Anas Rahmad Hidayat (STIKES DUTAGAMA KLATEN, 2013)
Background: One of the health development efforts is the revitalization program Integrated Service Post (IHC). IHC activity is an effort to increase community participation in creating a healthy toddler. In the course of IHC in the Village Kalikebo Trucuk Klaten district cadre role to give effect to the implementation of integrated health activities. Purpose: The purpose of this study was to determine the relationship of the role of cadres by improving integrated health services in rural Kalikebo Trucuk Klaten district. Methods: This study was an observational study with cross sectional analytic. The population in this study were all cadres in the village Kalikebo Trucuk Klaten district as many as 50 people. Samples was determined by saturation technique and obtained a sample of 50 people. Methods used in collecting data by answering the checklist and data collection is done once in a while (time motion study). The technique of data analysis using Chi-Square test.Results: The results showed that there was a significant correlation between the effort to increase the role of cadres in the village posyandu Kalikebo Trucuk Klaten district, with a significance value p-value of 0.000, because (0.000 <0.05), then HO is rejected and Ha accepted. This means that there is a significant correlation between the effort to increase the role of cadres in the village posyandu sub Kalikebo. Trucuk district Klaten. The role of cadres good effect on service improvement posyandu. That is, with a good level cadres role then led to increased posyandu well too. Conclusion: There is a significant relationship between the role of the cadre of the service improvement efforts Kalikebo neighborhood health center in the village of the district. Trucuk district Klaten.